War and society in colonial Zambia, 1939-1953 - Tembo, Alfred, 1978- (War and militarism in African history., 2021)
"The first major study of its kind, this book shows-from a Zambian perspective-how Northern Rhodesia, then a British colony, organized and deployed human, military, and natural resources during the Second World War. New research and oral histories further demonstrate the war's social and industrial impact on Zambia in the immediate postwar period"--